Daya Hambat Antibakteri Ekstrak Akar Rumput Bambu (Lophatherum gracile) terhadap Bakteri Streptococcus sp Secara In Vitro - Pipi Deka Dianci; Wulandari Wulandari; Deah Lara Santi; Harmoko Harmoko (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2021)
This study aimed to analyze the antibacterial activity of the root extract of the Suku Anak Dalam bamboo grass (Lophatherum gracile) against cough-causing bacteria (Streptococcus sp). The method used is laboratory-based experimental research with analytical descriptive type to test the root extract of bamboo grassroots on Streptococcus sp. Data analysis was carried out descriptively qualitatively by subtracting the diameter of the inhibition zone formed from the diameter of the disc that had been soaked with Lophatherum gracile extract. The treatments used consisted of 20%, 40%, 60%, 80%, 100% and positive control using amoxicillin. The results showed that at a concentration of 20%, the average inhibition zone formed was 2.03 mm, 40% concentration was 2.27 mm, 60% concentration was 2.61 mm, 80% concentration was 2.72 mm, 100% by 3.1 mm and positive control by 12 mm. In conclusion, bamboo grass root has a weak antibacterial ability and needs to be combined with other ingredients if you want to use it as cough medicine. Keywords: Antibacterial, Bamboo Grassroot, Cough, Anak Dalam Tribe, Streptococcus